Probing the Carboxyester Side Chain in Controlled Deactivation (−)‑Δ8‑Tetrahydrocannabinols - Nikas, Spyros P; Sharma, Rishi; Paronis, Carol A; Kulkarni, Shashank; Thakur, Ganesh A; Hurst, Dow; Wood, JodiAnne T; Gifford, Roger S; Rajarshi, Girija; Liu, Yingpeng; Raghav, Jimit Girish; Guo, Jason Jianxin; et al. (Journal of medicinal chemistry, 2015)
We recently reported on a controlled deactivation/detoxification approach for obtaining cannabinoids with improved druggability. Our design incorporates a metabolically labile ester group at strategic positions within the THC structure. We have now synthesized a series of (−)-Δ8-THC analogues encompassing a carboxyester group within the 3-alkyl chain in an effort to explore this novel cannabinergic chemotype for CB receptor binding affinity, in vitro and in vivo potency and efficacy, as well as controlled deactivation by plasma esterases. We have also probed the chain’s polar characteristics with regard to fast onset and short duration of action. Our lead molecule, namely 2-[(6aR,10aR)-6a,7,10,10a-tetrahydro-1-hydroxy-6,6,9-trimethyl-6H-dibenzo[b,d]pyran-3-yl]-2-methyl-propanoic acid 3-cyano-propyl ester (AM7438), showed picomolar affinity for CB receptors and is deactivated by plasma esterases while the respective acid metabolite is inactive. In further in vitro and in vivo experiments, the compound was found to be a remarkably potent and efficacious CB1 receptor agonist with relatively fast onset/offset of action.